Snakebite case management: a cohort study in Northwest Ethiopia, 2012-2020 - Rezika Mohammed; Johan van Griensven; Addisu Alemu Ambaw; Tesfaye Yesuf Yimer; Kudakwashe Collin Takarinda; Edward Mberu Kamau; Maria Zolfo; Veerle Vanlerberghe (Journal of Infection in Developing Countries)
Introduction: Timely and appropriate management of snakebites in the tropics is a lifesaver. Many snakebite patients are being bitten in remote rural areas and do not manage to get in due time to healthcare facilities. This study assessed the clinical features and the risk factors associated with treatment outcomes of snakebite patients admitted at two hospitals in the Northwest of Ethiopia.